Letramento probabilístico : um olhar sobre as situações de aprendizagem do caderno do professor - Custódio, Leandro Aparecido Alves (2017)
The aim of this research was to analyze the concept of probability through the diversity of semiotic representation records arranged in the statement of the tasks (learning situations) contained in the second volume of the Teacher's notebook for the second high school series and their possible contributions to the development of probabilistic literacy. The study was based on Raymond Duval's Theory of Semiotic Representations and on the Probabilistic Letters of Iddo Gal. We sought to answer the following research questions: What and how are the records of semiotic representation in the learning situations proposed in the teacher's book? Do such records contribute to the development of probabilistic literacy? In order to fulfill the purposes of our work, we resorted to bibliographical and documentary research and based on our theoretical contributions, we analyzed the content of four learning situations. Among the several records of semiotic representation, the tree diagram was little explored in the proposed tasks. The mobilization and coordination of records of this nature has the function of contributing to the construction of concepts, but in the case of problems of combinatorial analysis, they did not present contributions to the development of probabilistic literacy, due to the absence of internal connections between the basic notions of With the calculation of probabilities.